Seeking help from weak ties through mediated channels: Integrating self-presentation and norm violation to compliance. (October 2018) - Rui, Jian Raymond; Li, Siyue
Abstract: Seeking help from weak ties via information communication technology (ICT) can be challenging. Drawing upon the self-presentation literature and norm violation theory, this study examines how the level of anticipated future interaction (AFI) with weak ties and the choice of channel for seeking help from them — email, texting, and voicemail — affect their compliance with these requests. Results from a between-subjects experiment ( N = 398) show that self-presentational concern fully mediate the impact of AFI on compliance. Additionally, compared to email and texting, making such requests via voicemail is perceived as less normative, resulting in the reduced likelihood of compliance. These findings provide implications about using ICT to seek social support and promote pro-social acts. Highlights: Self-presentational concern facilitates compliance with weak-tie request. Anticipation of future interaction heightens self-presentational concern. Violating norms of channel usage lowers compliance with weak-tie request. Seeking help from weak ties via voicemail violates norms.